2015
DOI: 10.1007/s00702-015-1464-7
|View full text |Cite
|
Sign up to set email alerts
|

TrkB blockade in the hippocampus after training or retrieval impairs memory: protection from consolidation impairment by histone deacetylase inhibition

Abstract: Relatively little is known about the requirement of signaling initiated by brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin receptor kinase B (TrkB), in the early phases of memory consolidation, as well as about its possible functional interactions with epigenetic mechanisms. Here we show that blocking TrkB in the dorsal hippocampus after learning or retrieval impairs retention of memory for inhibitory avoidance (IA). More importantly, the impairing effect of TrkB antagonism on consolidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Gene transcription for BDNF is stimulated by HDACis (Wu et al, 2008; Koppel and Timmusk, 2013), and systemic HDACi treatment increases protein levels of BDNF in the rat brain (Kim et al, 2009). In addition, administration of an HDACi into the hippocampus rescues the impairment of IA memory consolidation produced by TrkB inhibition (Blank et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene transcription for BDNF is stimulated by HDACis (Wu et al, 2008; Koppel and Timmusk, 2013), and systemic HDACi treatment increases protein levels of BDNF in the rat brain (Kim et al, 2009). In addition, administration of an HDACi into the hippocampus rescues the impairment of IA memory consolidation produced by TrkB inhibition (Blank et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Administration of HDACis lead to increased acetylation and enhanced gene expression in neurons, resulting in a facilitation of synaptic plasticity as well as formation and extinction of fear conditioning (Levenson et al, 2004; Lattal et al, 2007; Vecsey et al, 2007; Bredy and Barad, 2008; Stafford et al, 2012). Acute systemic or intrahippocampal administration of HDACis enhances IA memory consolidation and rescues IA deficits related to aging or models of memory impairment (Silva et al, 2012; Blank et al, 2014, 2015, 2016; Sharma et al, 2015; Petry et al, 2016). Epigenetic alterations in the lateral amygdala, including increased histone H3 acetylation, are involved in the formation and reconsolidation of memory for auditory fear conditioning in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The same group showed that the HDAC inhibitor NaB reversed impairments in memory consolidation (of the original memory) that were due to inhibition of the brain-derived neurotrophic factor (BDNF) tyrosine receptor kinase B (TrkB). However, deficits in memory reconsolidation induced by TrkB inhibition were not reversed by NaB (Blank et al, 2016). A possible explanation for this discrepancy in the finding is that the effect of HDAC inhibition on facilitating memory reconsolidation is restricted to fear conditioning and does not hold for inhibitory avoidance.…”
Section: Histone Modifications In Fear Reconsolidationmentioning
confidence: 97%
“…1. The general procedures for IA behavioral training and retention tests were described in previous reports [6,7] On training trials, the rats were placed on the platform and their latency to step down on the grid with all four paws was measured with a digital chronometer. Immediately after stepping down on the grid, the rats were given a 0.4-mA, 3.0-s footshock and then removed from the apparatus immediately afterward.…”
Section: Inhibitory Avoidance (Ia)mentioning
confidence: 99%
“…Rats were implanted under anesthesia with isoflurane (vaporized in 100% oxygen, at a dose of 5% for induction and 2% for maintenance, in a fraction of 0.5 l/min) with bilateral 8-mm, 23-gauge guide cannulae aimed 1.0 mm above the dorsal hippocampus, as described previously [6,7]. Coordinates (anteroposterior, -4.3 mm from bregma; mediolateral, ±3.0 mm from bregma; ventral, -2.0 mm from skull surface) were obtained from the atlas of Paxinos and Watson [38].…”
Section: Surgerymentioning
confidence: 99%